Social media security : leveraging social networking while mitigating risk - Cross, Michael, 1965- (Amsterdam, [Netherlands] : Syngress, 2013)
'Technology has become less about connecting computers, and more about connecting people. A major reason for this evolution is that the use of social media has exploded in the last few years, making it easier for individuals and businesses to contact others and get their messages across to large audiences. According to a July 2012 study by the McKinsey Global Institute, there are 1.5 billion people using social networking throughout the world, with 80% of them interacting regularly with other social media users. Its popularity and the drive to reach to customers has lead to 70% of companies using social media. Social technology has become a way of life in how we socialize and do business. However, while social media is a powerful tool for interacting with others, many people and organizations have jumped into using it without considering the risks. The threats you face can affect your safety, your job and your business. In this book, we'll show you how to deal with the potential dangers, but before that, let's start by understanding what social media is and how it's evolved'--
Machine generated contents note: Introduction Defining Social Networking Why Social Media Is Important Defining the Organization's Goals for Social Networking Use Risks Present in Social Networking Mitigating Risks Continuous Social Networking Security Summary.
Includes bibliographical references and index.
Keywords: Social media -- Security measures; Online social networks -- Security measures; Risk management -- Social aspects; Computer security